Improving Students’ English-Speaking Abilities Through TikTok Applications - Putri, Alya; Ariyani, Amra; Sofyan, Ryan Rayhana (Journal of Excellence in English Language Education, 2026)
This research investigates the TikTok application in improving English speaking abilities among secondary school students at SMPN 6 Makassar. Employing a quantitative method with a pre-experimental design, the study utilized a one-group pre-test and post-test approach. A sample of 36 seventh-grade students from class VII-B participated in the study. The independent variable was the use of the TikTok application, while the dependent variable was students’ speaking ability, measured through speaking tests administered before and after a four-meeting treatment. The treatment involved project-based learning activities using TikTok, focusing on vocabulary related to food, ingredients, and cooking tools. Data analysis using a paired sample t-test revealed a significant improvement in students' speaking abilities after the intervention (p < .001). The mean score increased from 63.11 in the pre-test to 78.50 in the post-test. These findings suggest that the TikTok application is a potentially effective tool for enhancing speaking skills in EFL classrooms. The study recommends integrating TikTok into speaking curricula and encourages further research with control groups and longer intervention periods.